Understanding the Reaction Mechanism of Glycerol Hydrogenolysis over a CuCr2O4 Catalyst. Issue 2 (20th December 2016) - Yun, Yang Sik; Kim, Tae Yong; Yun, Danim; Lee, Kyung Rok; Han, Jeong Woo; Yi, Jongheop
Abstract: The reaction mechanism of glycerol hydrogenolysis to 1, 2‐propanediol over a spinel CuCr2 O4 catalyst was investigated by using DFT calculations. Theoretical models were developed from the results of experimental characterization. Adsorption configurations and energetics of the reactant, intermediates, final product, and transition states were calculated on Cu(1 1 1) and CuCr2 O4 (1 0 0). Based on our DFT results, we found that the formation of acetol is preferred to that of 3‐hydroxypropionaldehyde thermodynamically and kinetically on both surfaces. For glycerol hydrogenolysis to 1, 2‐propanediol, the CuCr2 O4 surface is less exothermic but more kinetically favorable than the Cu surface. The low activation barrier during the reaction on the CuCr2 O4 surface is attributed to the unique surface structure; the cubic spinel structure provides a stable adsorption site on which reactants are allowed to be dehydrated and hydrogenated easily with the characteristic adsorption configuration. The role of the Cu and Cr atoms in a CuCr2 O4 surface were revealed. The results of reaction tests supported our theoretical calculations. Abstract : Scratching the surface : The detailed mechanism for hydrogenolysis of glycerol is investigated over CuCr2 O4 catalyst by using DFT calculations. The roles of Cu and Cr are revealed, and experimental validation is performed.